2019
DOI: 10.33073/pjm-2019-057
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes of Bacillus subtilis Biomass on Biosorption of Iron (II) from Aqueous Solutions: Isotherm and Kinetic Studies

Abstract: Various microbial biomasses have been employed as biosorbents. Bacterial biomass has added advantages because of easy in production at a low cost. The study investigated the biosorption of iron from aqueous solutions by Bacillus subtilis. An optimum biosorption capacity of 7.25 mg of the metal per gram of the biosorbent was obtained by the Inductive Coupled Plasma Optical Emission Spectroscopy (ICP-OES) under the experimental conditions of initial metal concentration of 100 mg/l, pH 4.5, and biomass dose of 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In this study, based on the R 2 constant of pseudo-first and pseudo-second-order kinetics equations, the adsorption of lead and cadmium ions by extracted EPS has a heterogeneous diffusion manner. Similar results indicating that the adsorption process occurs by an ion-exchange mechanism (electron transfer) that affects the overall adsorption rate ( 41 , 55 58 ), which is compatible with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, based on the R 2 constant of pseudo-first and pseudo-second-order kinetics equations, the adsorption of lead and cadmium ions by extracted EPS has a heterogeneous diffusion manner. Similar results indicating that the adsorption process occurs by an ion-exchange mechanism (electron transfer) that affects the overall adsorption rate ( 41 , 55 58 ), which is compatible with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…The coefficient of the Freundlich model that is a criterion for adsorption intensity ( 52 ), indicates appropriate adsorption under experimental conditions and showed an acceptable adsorption process. Various other studies have reported that Freundlich isotherm models are better to explain the adsorption behavior of microorganisms ( 53 – 55 ). In this study, based on the R 2 constant of pseudo-first and pseudo-second-order kinetics equations, the adsorption of lead and cadmium ions by extracted EPS has a heterogeneous diffusion manner.…”
Section: Discussionmentioning
confidence: 99%
“…The results were in agreement with other studies which was also reported the Freundlich isotherm model to be well-fitted for Bacillus sp. ( Liu et al, 2013 ; Kanamarlapudi and Muddada, 2019 ). In another study, the same model was also observed to be opted by Lactobacillus fermentum for the biosorption of Cu ions ( Kargar and Shirazi, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the removal e ciency of Cd (II) by the dead pellet was signi cantly higher than live pellet. The increase in biosorbent dosage may aggregate or overlap, which means reducing the available binding sites, leading to decreased adsorption capacity [41]. The active sites on the cell surface cannot be fully applied, which has also decreased the adsorption capacity of the biosorbents [42].…”
Section: Effect Of Adsorption Parameters On Biosorptionmentioning
confidence: 99%